How to Estimate Food Prices and Diet Costs in Population-Based Studies? - de Mello, Aline Veroneze; Sarti, Flavia Mori; Fisberg, Regina Mara (Frontiers in Nutrition, 2021)
Health and nutrition surveys usually comprise detailed information on health characteristics and food consumption of certain population groups; however, the lack of data collection on food prices may pose challenges for estimation of diet costs. Household budget surveys (HBS) represent an opportunity to obtain data on food prices for nutrition surveys in diverse countries worldwide. Although HBS and health and nutrition surveys may correspond to different periods, the application of appropriate consumers’ prices indexes (CPI) allows to address changes in relative prices to perform the linkage between data of food consumption with information on food prices. Therefore, the aim of the study was to present methods for extraction and linkage of food prices data from the Brazilian HBS (2002-2003 and 2008-2009), using pairing features related to household characteristics to match the Health Survey of Sao Paulo (Inquérito de Saúde de Sao Paulo, ISA-Capital) 2003, 2008 and 2015. Data referring to household characteristics and food prices acquired by household members living in Sao Paulo municipality were selected from HBS datasets for integration with ISA-Capital dataset. Specific deflators referring to food items surveyed in Sao Paulo were obtained from the datasets of the Brazilian Broad Consumer Price Index (BCPI). Pairing criteria referring to time, location, and household characteristics were adopted to allow linking foods consumed by individuals in ISA-Capital with prices from foods acquired in HBS. Matching data on key pairing criteria (location/year/household income per capita/number of residents/family profile) resulted in linkage of 94.4% (2003), 92.6% (2008), 81.2% (2015). Following data linkage, it was possible to estimate diets costs per gram and calorie, including application of cooking and conversion factors. Data were presented international monetary unit under purchasing power parity (PPP) to allow comparison at international level. Thus, it was possible to estimate diet costs based on prices of food items through pairing-linkage of information from household surveys, like Brazilian HBS, with health and nutrition surveys lacking information on expenditures or prices, like ISA-Capital. Similar procedures may be used in diverse countries with availability of datasets of household expenditures and health-nutrition surveys, allowing researchers worldwide to associate diet quality with food demand.